Description of Community Satisfaction at Puskesmas Lok Bahu During The Implementation of Primary Care Integration - Zulhijrian Noor; Ratno Adrianto; Irfansyah Baharuddin Pakki (Mulawarman International Conference on Tropical Public Health, 2025)
Background : In January 2025, the Mayor's decree designated all Community Health Center in Samarinda as Primary Health Service Integration Implementers. The initiative aims offer comprehensive services the encompass all stage of life, from infancy to the erderly. It is expected that change will improve the quality of care and enhance community satisfaction. Puskesmas Lok Bahu measures satisfaction through the Community Satisfaction Survey in accordance with Permenpan No.14 of 2017. Over the past three years, satisfaction scores have shown some variation but have consistenly remain in the very good category. Objective : This reasearch aims to describe community satisfaction at Puskesmas Lok Bahu during the implementation of primary care integration. Research Methods/ Implementation Methods : This reasearch employs a descriptive method, utilizing secondary data collected from a community satisfaction survey in first semester of 2025 from 398 respondents at Puskesmas Lok Bahu Results : The Community Satisfaction Index stands of 89. The lowest score was related to serviced periode, which received at rating of 3.435, while the highest score were for handling complaints from service users and service rates, both of which scored 3.857. A notable issue with service timing was identified due to an insufficient number of medical personnel in relation to patient visits, the center had only two doctors, and one of whom also served as the head of Puskesmas Conclusion/Lesson Learned : It is recommended to consider the addition of medical personnel and to enhance the queuing system along with information technology solutions to effectively redice patient wait times.